Ethnomathematics: Mathematical ideas and educational values on the architecture of Sasak traditional residence - Lalu Muhammad Fauzi; Farida Hanum; Jailani Jailani; Jatmiko Jatmiko (Institute of Advanced Engineering and Science, 2022)
Sasak traditional architecture, including the shape of the structure, layout, and other supporting buildings, has references and rules in its designing and planning. Traditional residence is one of the cultural artifacts. A residence is not only built based on aesthetic values, but is also reviewed from strengths and values contained philosophically. Thus, this study aimed to describe mathematical ideas that are contained in the architecture of Sasak traditional residence as well as educational values in the culture that can be made as the initial step in designing learning processes at schools. This study was qualitative research conducted by using an ethnographic method. The informants in the study encompassed Adat figures, Adat stakeholders, and cultural experts who understand the culture of Sasak people. Participant observation, interview, documentation, and field record were the data collecting techniques used in the study. Findings showed the existence of mathematical ideas that are potential to be made as the initial step in learning mathematics contextually.